Systematic exploration of eczema‐associated paediatric diseases in a Chinese population of millions: A retrospective observation study - Huiwen Zheng; Jian Yang; Yuqing Feng; Huilong Duan; Lizhong Du; Qiang Shu; Haomin Li (Clinical and Translational Allergy, 2023)
Abstract Background Eczema is the most common form of dermatitis and also the starting point of atopic march. Although many eczema‐associated allergic and immunologic disorders have been studied, there remains a gap in the systematic quantitative knowledge regarding the relationships between all childhood disorders and eczema. This study aimed to systematically explore eczema‐associated childhood diseases using a real‐world, long‐term clinical dataset generated from millions of children in China. Methods Data were collected at 8,907,735 outpatient healthcare visits from 2,592,147 children between January 1, 2013, and August 15, 2019, at the largest comprehensive pediatric medical center in Zhejiang Province of China. The period prevalence differences in various pediatric diseases between children with and without eczema were used to test the independence of various pediatric disorders and eczema using Fisher's exact test. Bonferroni correction was used to adjust the p value in multiple testing. Odds ratio >2 with 95% confidence interval not including 1 and adjusted p < 0.05 was used to identify eczema‐associated diseases. Results Overall, 234 pediatric disorders were identified from more than 6000 different pediatric disorders. An interactive eczema‐associated disease map that has related quantitative epidemiological features called ADmap was published at http://pedmap.nbscn.org/admap. Thirty‐six of these disease associations have not been reported in previous studies. Conclusion This systematic exploratory study confirmed the associations of many well‐known diseases with eczema in Chinese children and also identified some novel and interesting associations. These results are valuable for the development of a comprehensive approach to the management of eczema in childhood.